Pengaruh Viral Marketing dan Brand Awareness terhadap Niat Beli pada Burger King Indonesia - Agatha Christy Avega Dumatri; Tias Andarini Indarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Competition for fast food restaurants is so fierce that companies need to find ways to do marketing wisely. Social media is one of the growing platforms that can be used as a marketing medium to reach consumers widely and quickly, which will lead to the emergence of consumer purchase intentions. This study aims to examine the effect of viral marketing and brand awareness on purchase intention. This study used 200 respondents with non-probability sampling techniques, and the method used was judgmental sampling were distributed using online questionnaires. Data were analyzed using multiple linear regression. This study found that viral marketing and brand awareness have a significant influence on purchase intention œBurger King Indonesia. Based on the result, it can be used as a recommendation œBurger King Indonesia in increase brand awareness more among competitors and have an impact to purchase intention.